2009
DOI: 10.1007/s11547-009-0380-z
|View full text |Cite
|
Sign up to set email alerts
|

Dolore acuto non traumatico del ginocchio nell’adulto: ruolo della risonanza magnetica

Abstract: Acute nontraumatic pain in the adult knee can be seen in many settings, such as transient bone marrow oedema syndrome (TBMOS), regional migratory osteoporosis (RMO), spontaneous osteonecrosis (SONK) and insufficiency fractures. Early differentiation among them is crucial to avoid unnecessary treatment. TBMOS and RMO are considered to be self-limiting conditions without longterm sequelae. On the other hand, the clinical course of SONK is thought to be dependent on the size of osteonecrosis. Recent data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Kesemenli et al [21] noted that SONK is regarded as a microfracture. Fotiadis et al [1] also noted that osteoporotic joint subchondral bone can lead to bone fragility, causing repeated microfractures, and its accumulation finally leads to osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kesemenli et al [21] noted that SONK is regarded as a microfracture. Fotiadis et al [1] also noted that osteoporotic joint subchondral bone can lead to bone fragility, causing repeated microfractures, and its accumulation finally leads to osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…There are many multifactorial pathogeneses of spontaneous osteonecrosis of the knee (SONK) which were derived from oeteoporosis and the continuous cycle, the repeated impact and stress on the subcondral bone [1]. These may induce microfracture, thus leading to subcondral insufficiency fracture [2-7] the prognosis of which is thought to be dependent on the lesion as detected in the MRI [8-12], few studies with the combination of BMD and MRI have been reported [13].…”
Section: Introductionmentioning
confidence: 99%
“…The terms: bone bruise, bone contusion and posttraumatic edema of the bone marrow have been seen for the last ten years in scientific literature and are in fact synonyms in the case of posttraumatic findings of bone marrow contusion. It must be emphasized however that edema of the bone marrow is not specific and that it can be present not only in trauma but also in infection, ischemia, migratory osteoporosis, early osteonecrosis, as a reaction to a neoplasm or even it can be idiopathic [2][3][4][5] . Sensitivity of MR imaging for detecting bone bruise of the knee is 83%-96% and specificity is 86%-96% 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The former advocated that high BMD overloaded the knee joint surface, causing joint cartilage damage that induces joint space narrowing as if it were severe degeneration. The latter suggested that subchondral bone of osteoporotic patients was exposed to direct mechanical stress via joint cartilage, causing the cancellous bone surrounding the subchondral bone to change, implying microfracture and osteonecrosis [9] and leading to promotion of valgus deformity of the knee, such as through joint surface decompression [10]. Furthermore, it is also thought that SONK is a faulty union of the bone due to ischemic change [11].…”
Section: Discussionmentioning
confidence: 99%